Role of Primary Care in Bridging Gaps in the Health Care System for Vulnerable Children in the United States of America: A Sickle Cell Disease Case Study - Natalie Weston; Alicia Chang; Alefiyah Malbari; Gunjan Dokania (SAGE Publishing, 2023)
Sickle cell disease (SCD) is a life-threatening condition. Given the nature of the disease and associated complications with high mortality and morbidity rates, it is imperative that patients are diagnosed in early infancy, are established with specialists and general pediatric care immediately, and receive continuity in care. A percentage of patients diagnosed with SCD fall within a vulnerable, at-risk population. This population may face greater social barriers that lead to missed or late diagnosis and therefore delayed management, significantly increasing the risk of morbidity and mortality. Screening tools such as state newborn screens help to identify the diagnosis early. However, patients in vulnerable, at-risk populations who are not established in the health care system may not receive timely communication about their illness and necessary next steps for care. We present a case of a 12-month-old female who is an example of one of the many patients who despite having undergone newborn screening, fell through the cracks due to social barriers including housing instability, food insecurity, and lack of access to transportation. This paper emphasizes the need for and provides a real example of the benefit of access to longitudinal primary care for vulnerable patients. We also demonstrate the role of primary care in clearing the care gaps and coordinating services quickly to ultimately prevent life-threatening complications specifically for children with previously undiagnosed chronic illnesses.